Ibn Khaldun Theory of Asabiyyah and the Rise and Fall of the Mughals in South Asia - Wazir, Asmat; Shakirullah Dawar; Khan, Hamayun; Khalid, Abda (Journal of Al-Tamaddun, 2022)
Abdur Rehman Ibn Khaldun was born on May 27, 1332, in Tunis into an Arab family of the Hadramaut which had first migrated to Spain, then to Morocco, and finally settled in Tunisia. He received a thorough education in theology and philosophy at the University (madrasa) of Tunis. At the age of twenty, he entered upon his chequered career, beginning as a secretary to the Sultan of Tunis. He served in various capacities and thus gained a versatile experience that helped him widening his understanding of human nature and political systems. Indeed, he was a prolific writer and scholar by leaving rich treatises on sociology, economics, history, politics, philosophy, and other disciplines. He propounded the theory of Asabiyyah: stemming out from blood lineage, common interests, common geography, and religion as a binding force and an ultimate factor of causing upswing and tumble to a dynasty or a state and thus he provided solid foundations to understand systematically the phenomenon of the rise and fall of dynasties and establishment of states and the factors which bring an ultimate decline to it. An attempt has been made in this article whilst applying this theory of Asabiyyah on the rise and fall of Mughals in South Asia. Founded by Babur in 1526, the Mughal Empire in India is divided into five periods as per the stages of Ibn Khaldun’s theory of Asabiyyah and each period is presented analytically particularly in terms of the Asabiyyah. Thus, this article presented the Khaldun’s cycle of the dynasty on the Mughal Empire who fulfilled its five stages on the soil of India.